Labeling of sustainable beef products in Latin America and the Caribbean: Initiatives and developments - Moreno, Leonardo; Díaz, Manuel F.; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2021)
The objective of this policy brief is to identify and analyze the current status and recent developments of sustainability labels for beef products in Latin America and the Caribbean (LAC) with the aim of understanding the measures adopted by the sector to respond to the demand of citizens regarding environmental, social, and economic issues that come along with the sustainable intensification of the sector.